Reports recorded with hidden cameras as a special course of unlawful interference in the right to privacy - Moreno Bobadilla, Ángela (2019)
The jurisprudence sitting by the Spain Constitutional Court in 2012, about the reports recorded with hidden cameras is clear and firm: the use of these techniques can´t be considered in all cases investigative journalism, so it could be only used when this is the only way to obtain this information of public interest, and in the all of the other cases that situation will be a unlawful interference in the right to privacy.